2010
DOI: 10.1021/jp907697f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of Glass-Forming Bay-Substituted Perylenediimide Derivatives

Abstract: A series of perylenediimide-based small molecules (PDI1-PDI5) containing electron-deficient groups in the bay region were synthesized and characterized. The PDI derivatives were found to be capable of forming molecular glasses with glass transition temperatures ranging from 50 to 102 degrees C. Detailed investigations of the optical properties of the synthesized derivatives were performed and compared with those obtained from quantum chemical calculations. Optimized molecular structures of the PDI derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The solubility of the ligands and their respective metal complexes are comparable: 1 and 3 are very soluble in toluene, CH 2 Cl 2 , and benzonitrile, but they are less soluble in butyronitrile and only 3 is soluble in acetonitrile, and in these two latter solvents the UV-Vis spectra show evidence of PDI aggregation (28,29). Dyad 2 and ligand 4 are soluble in the entire range of solvents, as a result of the 3-pentyl tail at the imide that hinders π-π stacking of PDI aromatic cores (30) and the direct attachment of the phenyl side-groups, which may cause even greater distortion of the PDI core from planarity relative to the phenoxy-substituted dyes (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of the ligands and their respective metal complexes are comparable: 1 and 3 are very soluble in toluene, CH 2 Cl 2 , and benzonitrile, but they are less soluble in butyronitrile and only 3 is soluble in acetonitrile, and in these two latter solvents the UV-Vis spectra show evidence of PDI aggregation (28,29). Dyad 2 and ligand 4 are soluble in the entire range of solvents, as a result of the 3-pentyl tail at the imide that hinders π-π stacking of PDI aromatic cores (30) and the direct attachment of the phenyl side-groups, which may cause even greater distortion of the PDI core from planarity relative to the phenoxy-substituted dyes (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The geometries ( Fig. S5 †) of the compounds 2 and 4 were optimized by adopting B3LYP method with 6-31G** basic set 36,37 via energy minimization. The twist angles between the two naphthalenoid moieties of 2 and 4 are 22.11 and 21.83 respectively, which are close to the reported value in literature.…”
Section: Photophysical Properties In Solutionmentioning
confidence: 99%
“…An alternative approach consists in designing PDI derivatives (or electron acceptor materials in general) that form thin films that remain amorphous. 26,27 While amorphous solids possess no long-range periodical order, intermolecular interactions, such as the -stacking of aromatic moieties, can nonetheless be present and regulate to a certain degree the organization at the molecular level, with a continuous material that is exempt of grain boundaries. As with the majority of small molecules, most PDI derivatives readily crystallize.…”
Section: Introductionmentioning
confidence: 99%
“…As with the majority of small molecules, most PDI derivatives readily crystallize. 26,27 However, it was demonstrated that strategic molecular design can hinder the process of crystallization, resulting in molecular materials that can remain in the amorphous state for extended (sometimes indefinite) periods of time. This class of materials are known as molecular glasses, or amorphous molecular materials, and combine the monodisperse nature of small molecules with the processability of polymers.…”
Section: Introductionmentioning
confidence: 99%